Consumer Behaviour and Brand Preference towards Onida Television-An Empirical Study with Reference to Karur, Tamil Nadu - Kathirvel, N.; Chandrasekaran, N. (Indian Journal of Marketing, 2009)
The television is a wonderful means of mass communication invented by J.L.Baird in 1926. Now our home has become a Cinema Hall. A Television is an audio-visual medium which enables us to hear and watch a variety of programmes, both live and recorded. The industries which produce the electronic devices and appliances for the use and conveniences of their customers are known at the Electronic industries. This industry manufactures varied forms of essential electronic appliances such as televisions to satisfy the wants of mankind. Now-a-days, televisions have become an essential item for mass based usage. They are manufactured in different sizes so as to meet the needs of various groups of people. They are usually rated with internal total mechanism and the television mechanism.